1986
DOI: 10.1152/ajpendo.1986.250.3.e231
|View full text |Cite
|
Sign up to set email alerts
|

A direct growth effect of growth hormone in rat hindlimb shown by arterial infusion

Abstract: We have developed a method for infusing substances into one hindlimb of the rat via the arterial supply. A catheter attached to an osmotic minipump is inserted into the right superior vesical artery and advanced to the junction of the right common iliac artery. This arrangement permits either constant or pulsatile infusion for 7 days. We employed this method to study the direct action of rat growth hormone (rGH) on the proximal tibial epiphysial plate in hypophysectomized rats. Infusion of neither the solvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
35
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 16 publications
3
35
0
Order By: Relevance
“…Husbandry conditions and anesthetics used were as described (43). Some of the rats were made diabetic by giving them an intrajugular injection of streptozotocin (65 mg per kg of body weight) on each of 2 consecutive days to destroy the beta cells of the pancreatic islets (44).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Husbandry conditions and anesthetics used were as described (43). Some of the rats were made diabetic by giving them an intrajugular injection of streptozotocin (65 mg per kg of body weight) on each of 2 consecutive days to destroy the beta cells of the pancreatic islets (44).…”
Section: Methodsmentioning
confidence: 99%
“…Details of the procedures used to construct the catheters and to attach them to the osmotic minipumps were described (43). The methods used by Mick and Nicoll (47) to catheterize the jugular vein (JV) and the HPV of pigeons were modified for use in the rat.…”
Section: Methodsmentioning
confidence: 99%
“…Although most of the early evidence in support of this theory was derived from in vitro work, Schoenle et al (5) recently demonstrated a dose-related growth-promoting effect of systemically infused human somatomedin (hSm) on the proximal tibial epiphyseal plate of hypophysectomized rats. However, a local effect of GH on tibial cartilage growth has also been demonstrated in hypophysectomized rats in vivo by direct injection into the proximal tibial epiphyseal plate (6,7), by intraarticular injection into the knee joint or administration into the epiphysis by implanted cannula (8), and by chronic infusion into the arterial supply of one hindlimb (9). In addition, numerous cells and tissues have been shown to produce somatomedins in vitro, either spontaneously or in response to GH (10)(11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…To investigate this possibility we used the system of Schlechter et al (9), which permits chronic infusion into the arterial supply of one hindlimb of a rat. With this procedure, we have demonstrated a direct growth-promoting effect of human somatomedin C (hSm-C) on the proximal tibial epiphyseal plate of hypophysectomized rats.…”
mentioning
confidence: 99%
“…Growth hormone increases longitudinal bone growth by stimulating cell differentiation in the germinal zone of the growth plate (Isaksson et al 1982, Schlechter et al 1986, Nilsson et al 1987, Isaksson et al 1988. Callus formation in healing diaphyseal fractures shows many similarities with the bone formation of the growth plate (Mindell et al 1971, Page et al 1986).…”
mentioning
confidence: 99%